Hunting the Jackal : A Special Forces and CIA Ground Soldier's Fifty-Year Career Hunting America's Enemies - Waugh, Billy with Keown, Tim (New York William Morrow, 2004)
A soldier who has served with the U.S. Army Special Forces and the CIA recounts his half-century career working against American adversaries, including the infamous terrorist knows as Carlos, and Osama bin Laden.
Include Acknowledgments
Keywords: Waugh, Billy, -- 1929- -- United States. -- Central Intelligence Agency -- Biography -- United States. -- Army. -- Special Forces -- Biography